2003
DOI: 10.1103/revmodphys.75.715
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence, einselection, and the quantum origins of the classical

Abstract: Decoherence is caused by the interaction with the environment which in effect monitors certain observables of the system, destroying coherence between the pointer states corresponding to their eigenvalues. This leads to environment-induced superselection or einselection, a quantum process associated with selective loss of information. Einselected pointer states are stable. They can retain correlations with the rest of the Universe in spite of the environment. Einselection enforces classicality by imposing an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

53
4,219
1
26

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,728 publications
(4,406 citation statements)
references
References 300 publications
53
4,219
1
26
Order By: Relevance
“…In this letter, we report on the realisation, with atoms, of a HOM experiment closely following the original protocol. This opens the prospect of testing Bell's inequalities involving mechanical observables of massive particles, such as momentum, using methods inspired by quantum optics 6,7 , with an eye on theories of the quantum-to-classical transition [8][9][10][11] . Our work also demonstrates a new way to produce and benchmark twin-atom pairs 12,13 that may be of interest for quantum information processing 14 and quantum simulation 15 .…”
mentioning
confidence: 99%
“…In this letter, we report on the realisation, with atoms, of a HOM experiment closely following the original protocol. This opens the prospect of testing Bell's inequalities involving mechanical observables of massive particles, such as momentum, using methods inspired by quantum optics 6,7 , with an eye on theories of the quantum-to-classical transition [8][9][10][11] . Our work also demonstrates a new way to produce and benchmark twin-atom pairs 12,13 that may be of interest for quantum information processing 14 and quantum simulation 15 .…”
mentioning
confidence: 99%
“…U nderstanding and controlling the coherence of multispin-qubit solid-state systems is crucial for quantum information science [1][2][3] , basic research on quantum many-body dynamics 4 and quantum sensing and metrology [5][6][7][8][9] . Examples of such systems include nitrogen-vacancy (NV) colour centres in diamond 10 , phosphorous donors in silicon 11 and quantum dots 12 .…”
mentioning
confidence: 99%
“…However, it can be shown that the characteristic timescale of the state vector collapse, known as the ''decoherence time'', is much shorter than any other characteristic dynamic timescale of the system. 33 A logical conclusion is that the state vector ''collapse'' |c s i -|a n i of the system is a consequence of the systemdevice interaction. During the measurement process the system and environment wave vectors become entangled and no longer evolve independently.…”
Section: Ferdinand C Grozemamentioning
confidence: 99%
“…During the measurement process the system and environment wave vectors become entangled and no longer evolve independently. 33 However, information transfer usually associated with measurements is a common result of almost any interaction of the system with its environment. Thus, one can imagine that the environment constantly ''measures'' any non-isolated system, and any system state |c s i that is not an eigenstate of an observable quickly collapses into one that is.…”
Section: Ferdinand C Grozemamentioning
confidence: 99%
See 1 more Smart Citation